2024
DOI: 10.1007/s11606-023-08579-5
|View full text |Cite
|
Sign up to set email alerts
|

What Clinicians and Researchers Should Know About the Evolving Field of Advance Care Planning: a Narrative Review

Ryan D. McMahan,
Susan E. Hickman,
Rebecca L. Sudore

Abstract: Advance care planning (ACP) has been recognized as crucial by patients, families, and clinicians; however, different definitions and measurements have led to inconsistencies in practice and mixed evidence in the literature. This narrative review explores ACP’s evolution, innovations, and outcomes using thematic analysis to synthesize data from randomized controlled trials, reviews, and editorials. Key findings include (1) ACP has evolved over the past several decades from a sole focus on code status and advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Over the last half decade, a previously harmonious general consensus around benefits associated with advance care planning (ACP) has taken a quick turn into dissonance. ACP is a process that supports adults of any age and with any stage of illness to better understand and share their unique values, goals, and preferences for future medical care 1 and is currently beset by controversy. A landmark editorial by Morisson et al 2 published in 2021 highlighted escalating concerns about the limitations of ACP and concluded that "ACP does not improve end-of-life care" and "clinical and research communities should learn from the evidence…and proceed with different approaches for improving care for seriously ill patients."…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last half decade, a previously harmonious general consensus around benefits associated with advance care planning (ACP) has taken a quick turn into dissonance. ACP is a process that supports adults of any age and with any stage of illness to better understand and share their unique values, goals, and preferences for future medical care 1 and is currently beset by controversy. A landmark editorial by Morisson et al 2 published in 2021 highlighted escalating concerns about the limitations of ACP and concluded that "ACP does not improve end-of-life care" and "clinical and research communities should learn from the evidence…and proceed with different approaches for improving care for seriously ill patients."…”
mentioning
confidence: 99%
“…Consequently, clinicians, researchers, policy makers, and patients and their families have been debating the ongoing role of ACP in provision of patientcentered and goal-concordant care. 1,3,4 These debates have centered on conceptual limitations to ACP, such as the limitations of using a static document to delineate evolving treatment preferences and the nonlinear nature of end-of-life care. Focus has shifted from explicit documentation of concrete preferences toward the designation of surrogates and promotion of shared decisionmaking, particularly ways to better prepare surrogates for "in the moment decision-making."…”
mentioning
confidence: 99%
See 1 more Smart Citation